Nuclear shape coexistence in 193Hg - Fotiades, N.; et al., - (HNPS Advances in Nuclear Physics, 2020)
Excited states of the 193Hg nucleus have been investigated by the reaction 150Nd(48Ca,5n) at a beam energy of 213 MeV. The level scheme has been extended up to 10.7 MeV. Three different level pattern regions have been identified. A lower region with rotational bands, an intermediate region with single-particle character and an upper region with sequences of dipole transitions. The nature and the corresponding nuclear shape in these regions are discussed and compared with similar phenomena in the neighbouring nuclei.